Efficient Indium‐Doped TiOx Electron Transport Layers for High‐Performance Perovskite Solar Cells and Perovskite‐Silicon Tandems. Issue 4 (4th November 2016) - Peng, Jun; Duong, The; Zhou, Xianzhong; Shen, Heping; Wu, Yiliang; Mulmudi, Hemant Kumar; Wan, Yimao; Zhong, Dingyong; Li, Juntao; Tsuzuki, Takuya; Weber, Klaus J.; Catchpole, Kylie R.; et al.
Abstract : In addition to a good perovskite light absorbing layer, the hole and electron transport layers play a crucial role in achieving high‐efficiency perovskite solar cells. Here, a simple, one‐step, solution‐based method is introduced for fabricating high quality indium‐doped titanium oxide electron transport layers. It is shown that indium‐doping improves both the conductivity of the transport layer and the band alignment at the ETL/perovskite interface compared to pure TiO2, boosting the fill‐factor and voltage of perovskite cells. Using the optimized transport layers, a high steady‐state efficiency of 17.9% for CH3 NH3 PbI3 ‐based cells and 19.3% for Cs0.05 (MA0.17 FA0.83 )0.95 Pb(I0.83 Br0.17 )3 ‐based cells is demonstrated, corresponding to absolute efficiency gains of 4.4% and 1.2% respectively compared to TiO2 ‐based control cells. In addition, a steady‐state efficiency of 16.6% for a semi‐transparent cell is reported and it is used to achieve a four‐terminal perovskite‐silicon tandem cell with a steady‐state efficiency of 24.5%. Abstract : Solution‐processed, indium‐doped TiO x films are shown to be very effective electron transport/hole‐blocking layers for high‐performance perovskite cells. Doping improves the conductivity and work‐function energy alignment at the ETL/perovskite interface, leading to high fill‐factor and open‐circuit voltage. An efficiency of ≈19.3% is demonstrated for a perovskite cell, and a steady‐state efficiency of 24.5% is presented for a four‐terminal perovskite‐silicon tandem cell.